2014
DOI: 10.1097/bsd.0b013e31828f9da1
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaveric Radiographic Analysis on the Effect of Extreme Lateral Interbody Fusion Cage Placement With Supplementary Internal Fixation on Indirect Spine Decompression

Abstract: The radiographic results reported here using a cadaveric model add validity to the underlying rationale described for the minimally invasive lateral approach technique. Increases in disk height, foraminal and canal areas were not dependent on cage positioning within the disk space. As intraoperative placement of a cage in the central portion of the disk is an easier and safer technique, our results suggest that central placement may be preferable in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 10 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…Specifically, in the acute term, we noted 24%, 31%, 67%, and 7% increases in right and left foraminal area, disc height, and canal area, respectively. These acute findings are in agreement with our prior radiographic findings in cadaveric lumbar spines instrumented with laterally placed cages and supplemental internal fixation [13]. Our in vitro study results indicated increases in disc height ([ 30%), foraminal area ([ 35%), and canal area ([ 30%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, in the acute term, we noted 24%, 31%, 67%, and 7% increases in right and left foraminal area, disc height, and canal area, respectively. These acute findings are in agreement with our prior radiographic findings in cadaveric lumbar spines instrumented with laterally placed cages and supplemental internal fixation [13]. Our in vitro study results indicated increases in disc height ([ 30%), foraminal area ([ 35%), and canal area ([ 30%).…”
Section: Discussionsupporting
confidence: 91%
“…In a previously published cadaver study [13], we demonstrated that interbody cage placement through the lateral transpsoas approach increased disc height, foraminal areas, and central canal area when compared to the noninstrumented lumbar spine. In a separate biomechanical study, we demonstrated that pedicle screw and rod instrumentation provided the best limitation to motion of the spinal segments [15].…”
Section: Introductionmentioning
confidence: 59%
“…14 , 15 Surgical invasiveness was defi ned using an invasiveness index for spine surgery developed by Mirza et al . [28][29][30][31] This approach involves transpsoas access to the anterior lumbar vertebral column, and has been associated with lumbar plexus injury and persistent neurological defi cits. However, the risk of specifi c intraoperative procedures has not been assessed before.…”
Section: Discussionmentioning
confidence: 99%
“…LLIF offers several advantages over posterolateral fusion, including indirect foraminal decompression and correction of spinal alignment (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%